Mechanisms of fertility failure in high yielding dairy cows - Mohammed, Zeravan-Abdulrazaq (2016)
Reproductive tract inflammatory diseases (RTID) of dairy cows are common worldwide and have been associated with a decrease in reproductive performance. The aims of this thesis were: (1) to quantify the effect of RTID on reproductive performance using data from 80 dairy herds across England and Wales, and from the University of Nottingham Dairy Centre; (2) to determine the effect of endometritis on the normality of post-partum milk progesterone profiles; (3) to investigate the association between endometritis and luteal vasculature and protein expression of steroidogenesis enzymes ex vivo; (4) to determine the expression of LPS-associated receptors including TLR4, CD14 and MD-2 in bovine CL using multiplex PCR; (5) to investigate the dose dependent effects of LPS on luteal endothelial cell vasculature in vitro and protein expression of steroidogenesis enzymes. Data analysis of 59118 cows from 80 dairy herds across England and Wales showed 12% prevalence of RTID from 2000-2007 (P<0.001). Cows with RTID had significantly longer intervals from calving to both first service and to conception by about 5 days (P<0.001) and 22 days (P<0.001), respectively. Moreover, cows with RTID had a lower conception rate to 1st service by 14% (P<0.001) and required more services per conception about 1 service more (P<0.001). In addition, they were 1.2 times more likely to be exited from the herd (P<0.001), and had higher 305d milk yield (P<0.01). Furthermore, this study analysed data from 708 cows at Nottingham dairy centre showed about 15% of prevalence of RTID form 2008-2014 (P<0.001). Similar effects were observed in the Nottingham dairy centre. However, only the day to 1st service was significant (P<0.001). The association between endometritis and milk progesterone profiles was investigated to establish the importance of endometritis on postpartum ovarian activity. Endometritis increased the incidence of atypical progesterone profile with prolonged luteal phase being the most affected. In the ex vivo study, there was a negative association between presence of endometritis with luteal vasculature, CL size, luteal progesterone content and quantification of steroidogenic enzyme expression. Endometritis caused significant inhibition in the degree of luteal vasculature, progesterone content and protein expression of steroidogenic enzymes by corpora lutea. LPS has been implicated in influencing ovarian function. Multiplex PCR showed that LPS receptors (TLR4, CD14, and MD-2) are expressed in bovine CL at all stages of CL development, indicating that CL could be a target for LPS action. A physiological cell culture system was consequently utilised to examine the effect of LPS on luteal endothelial cell network formation, progesterone (P4) production by luteal cells and steroidogenic enzyme expression in vitro. Treatment with VEGFA/FGF2 increased progesterone production by luteal cells (P<0.001). Moreover, progesterone production increased significantly from day 3-9 of culture. Under both basal condition and/or angiogenic stimulus (VEGFA/FGF-2), LPS (0.01, 0.1, 1 and 10 µg/ml) had no effect on P4 production by luteal cells on day 3, 5, and 9 of culture. LPS significantly inhibited luteal endothelial cells network formation. This was due to inhibition of endothelial cell proliferation and increasing endothelial cell apoptosis (P<0.001). In summary, the adverse impact that endometritis has on dairy cow fertility was identified by this work. This work offers a greater understanding of the effect of endometritis on dairy cow’s reproductive performance, early luteal development and function. In particular, this work provides evidence of a novel effect of endometritis on bovine luteal development and adequacy. It also offers further awareness into the role of LPS in terms of its negative effect on luteal endothelial cell angiogenesis and steroidogenesis.